Innovative Animal Model of DSS-Induced Ulcerative Colitis in Pseudo Germ-Free Mice - Sona Gancarcikova; Stanislav Lauko; Gabriela Hrckova; Zuzana Andrejcakova; Vanda Hajduckova; Marian Madar; Livia Kolesar Fecskeova; Dagmar Mudronova; Kristina Mravcova; Gabriela Strkolcova; Radomira Nemcova; Jana Kacirova; et al. (Cells, 2020)
The aim of this study was to investigate the use of a standardized animal model subjected to antibiotic treatment, and the effects of this treatment on the course of dextran sodium sulphate (DSS)-induced colitis in mice. By decontamination with selective antibiotics and observation of pathogenesis of ulcerative colitis (UC) induced chemically by exposure of mice to various concentrations of DSS, we obtained an optimum animal PGF model of acute UC manifested by mucin depletion, epithelial degeneration and necrosis, leading to the disappearance of epithelial cells, infiltration of lamina propria and submucosa with neutrophils, cryptitis, and accompanied by decreased viability of intestinal microbiota, loss of body weight, dehydration, moderate rectal bleeding, and a decrease in the selected markers of cellular proliferation and apoptosis. The obtained PGF model did not exhibit changes that could contribute to inflammation by means of alteration of the metabolic status and the induced dysbiosis did not serve as a bearer of pathogenic microorganisms participating in development of ulcerative colitis. The inflammatory process was induced particularly by exposure to DSS and its toxic action on compactness and integrity of mucosal barrier in the large intestine. This offers new possibilities of the use of this animal model in studies with or without participation of pathogenic microbiota in IBD pathogenesis.